2010
DOI: 10.1038/leu.2009.284
|View full text |Cite
|
Sign up to set email alerts
|

Alloreactive microenvironment after human hematopoietic cell transplantation induces genomic alterations in epithelium through an ROS-mediated mechanism: in vivo and in vitro study and implications to secondary neoplasia

Abstract: We hypothesized that chronic tissue stress due to interaction of alloreactive donor cells with host epithelium after allogeneic hematopoietic cell transplantation (allo-HCT) may cause genomic alterations. We therefore analyzed 176 buccal samples obtained from 71 unselected allotransplanted patients for microsatellite instability (MSI). MSI was observed in 52% of allotransplanted patients but never in 31 healthy or autotransplanted controls. The patient age, the donor age, a female-tomale transplantation and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 43 publications
4
32
0
Order By: Relevance
“…A recent report showed that alloreactive microenvironment after HCT induces GI in epithelium through a reactive oxygen species (ROS)-mediated mechanism supports our results. 15 Finally, we have not studied any patients with secondary oral squamous cell malignancy. Faber et al 12 documented GI in 3 of 3 patients with secondary squamous cell malignancy and Themeli et al 15 reported GI in 5 of 6 patients with secondary epithelial cell malignancy.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report showed that alloreactive microenvironment after HCT induces GI in epithelium through a reactive oxygen species (ROS)-mediated mechanism supports our results. 15 Finally, we have not studied any patients with secondary oral squamous cell malignancy. Faber et al 12 documented GI in 3 of 3 patients with secondary squamous cell malignancy and Themeli et al 15 reported GI in 5 of 6 patients with secondary epithelial cell malignancy.…”
Section: Resultsmentioning
confidence: 99%
“…40 In addition, evidence suggests that chronic GVHD induces a chronic inflammatory state, leading to microsatellite instability and frequent genomic alterations in epithelial tissues, predisposing to development of cancers. 41,42 Several reports have shown increased risk of subsequent malignancy associated with chronic GVHD in FA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as MSCs, despite their known hypo-immunogenicity, respond to signals of local and systemic inflammation, we evaluated the effects of the milieu generated by alloactivated lymphocytes on HO-1 expression. 2,7,24 These "prelicensed" MSCs were subsequently assessed with regards to their ability to induce Tregs and to suppress T cells.…”
Section: Introductionmentioning
confidence: 99%